A Literature Review on Integrating Local Cultural Values into Curriculum Development - Chuzaimah; La Sunra; Syarifuddin Dollah (Universitas Islam Negeri Palopo, 2026)
This review examines how local cultural values have been incorporated into curriculum development by analyzing peer-reviewed articles, policy papers, and academic reports published between 2018 and 2025. Using an integrative literature review design supported by qualitative content analysis, the study synthesizes theoretical perspectives, implementation strategies, and empirical findings from both Indonesian and international contexts. The results indicate that integrating cultural elements into the curriculum strengthens students’ cultural identity, enhances learning engagement, and increases the contextual relevance of instructional materials. The analysis also shows that culturally responsive curriculum models contribute to more inclusive learning environments by acknowledging learners’ cultural backgrounds. However, the review identifies a persistent gap between policy ideals and classroom practice, particularly regarding teacher preparation, curriculum design, and resource availability. Many initiatives remain symbolic rather than transformative due to limited guidance on how cultural values should be embedded systematically at the curriculum level. This review highlights the need for stronger collaboration among educators, policymakers, and local communities to ensure sustainable curriculum integration practices that balance national standards with cultural specificity. Overall, the study contributes a consolidated framework for understanding cultural integration in curriculum development and clarifies the areas where further empirical investigation is still needed.